EFFECTS OF STREET TRADING ON URBAN AREAS IN NIGERIA - Gani, Bogoro Audu (IJRDO - Journal of Applied Management Science, 2015)
Street trading is a form of squatting that involves perpetual movement that mayoccur within established market places or around road intersections which resultsto several negative impacts on physical environment such as traffic congestion,environmental pollution, and aesthetically unpleasing environment. This studylooks at the effects on cities in Nigeria. Three urban areas Bauchi, Lagos and PortHarcourt were sampled to study the impact of street trading in Nigerian urbanareas. 100 questionnaires were administered to each of the three urban centersselected. It is found that 40.59% of streets traders are migrants from the ruralareas The study discovered that most of the streets traders indiscriminatelydisposed of their refuse by burning and dumping in the drainage there by blockingthe drainage channels causing flood during rainy season and 24.75% dumpedtheir waste right on the roadside. There is disorderliness in the arrangement ofdifferent methods used in displaying of items by street traders there by making thestudy area appear as an insightful and unpleasant urban environment thusdispleasing visual effect and 28.71% of streets traders encroached into the roadwith up to 1-1.5m and above causing serious traffic problem. The paperrecommends development of rural areas to reduce rural-urban migration,relocating those that encroached to in the road, and the provision of moveablerefuse collection points